2007
DOI: 10.2337/dc06-1899
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Adrenomedullin, Metabolic Factors, and Vascular Function in Individuals With Type 2 Diabetes

Abstract: CHEE FANG SUM, MBBS1 OBJECTIVE -Subjects with type 2 diabetes are at risk for vascular injury. Several vasoactive factors (e.g., angiotensin) have been implicated. We hypothesize that adrenomedullin, a novel vascoactive factor, is deranged in subjects with type 2 diabetes.RESEARCH DESIGN AND METHODS -Using a new immunoluminometric method, plasma midregional proadrenomedullin (MR-proADM) was measured in four groups of Chinese subjects: healthy (n ϭ 100, fasting plasma glucose [FPG] Ͻ5.6 mmol/l), impaired fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 50 publications
9
30
0
Order By: Relevance
“…So far, circulating ADM levels were only investigated in small cohorts of diabetic patients with inconsistent results (26,27,28). In line with our findings, Lim et al (29) reported increased MR-proADM levels in patients with T2D, which were related to chronic inflammation (hsCRP), lipids, and IR. We are the first to demonstrate that MR-proADM levels are highly correlated with MetS, suggesting that ADM may play a role in the pathogenesis of this disorder.…”
Section: Discussionsupporting
confidence: 78%
“…So far, circulating ADM levels were only investigated in small cohorts of diabetic patients with inconsistent results (26,27,28). In line with our findings, Lim et al (29) reported increased MR-proADM levels in patients with T2D, which were related to chronic inflammation (hsCRP), lipids, and IR. We are the first to demonstrate that MR-proADM levels are highly correlated with MetS, suggesting that ADM may play a role in the pathogenesis of this disorder.…”
Section: Discussionsupporting
confidence: 78%
“…However, in previous studies with groups of healthy individuals (18,23,28 ) and in septic patients (24 ), no sex difference was observed. Interestingly, our data showed that MR-proADM concentrations were lower in current smokers compared to nonsmokers or those having formerly smoked.…”
Section: Discussionmentioning
confidence: 83%
“…The identification of midregional proadrenomedullin (MR-proADM) has overcome these problems because it is a stable peptide possibly reflecting the concentration of ADM, is theoretically secreted in amounts equimolar to those of ADM, and most likely does not have any physiological effects that might explain its apparent stability (18,22 ). Although its detailed pathological role has not been fully explored, increased plasma concentrations of MR-proADM have been related to cardiac dysfunction, systemic inflammatory status, prevalent type 2 diabetes, and renal failure (22)(23)(24).…”
mentioning
confidence: 99%
“…8,9 As such, plasma concentration of AM was progressively increased in patients with impaired glucose tolerance, diabetes and diabetes with nephropathy. 28 In addition, an increase in AM was related to multiple metabolic factors. 28 AM and insulin resistance may conflict with each other.…”
Section: Discussionmentioning
confidence: 99%
“…28 In addition, an increase in AM was related to multiple metabolic factors. 28 AM and insulin resistance may conflict with each other. Specifically, decreased reactivity of AM may contribute to increased arterial stiffness during insulin resistance, and this alteration may accelerate the progression of arterial sclerosis in insulin resistance.…”
Section: Discussionmentioning
confidence: 99%